Pengaruh Tingkat Literasi Keuangan Syariah Terhadap Kinerja Pemasaran Bank Umum Syariah Guna Optimalisasi Kepercayaan Nasabah - Mochamad Yusuf; Rinda Asytuti (Velocity: Journal of Sharia Finance and Banking, 2022)
This study aims to analyze the effect of Islamic financial literacy level on the performance of Islamic banks in order to optimize customer trust. This research is classified as a type of qualitative descriptive research. The type of data used in this study is the type of primary data with data collection techniques in the form of observation and interviews. The results of this study indicate that the level of Islamic financial literacy plays an important role in the performance of Islamic banks. Good performance of Islamic banks gives customers confidence in Islamic banks. Keywords: Islamic Financial Literacy, Islamic Bank Performance, Trust